' - Rifki Sudai; Siswoyo; Murtaqib; Muhammad Shodikin (KHD Production, 2025)
Anxiety in patients undergoing Transurethral Resection of the Prostate (TURP) surgery can have a significant impact on the physiological and psychological aspects of the patient. Anxiety in preoperative patients can result in surgery being postponed or canceled. One effort that can be made to reduce anxiety levels in preoperative TURP patients is to provide SEFT therapy. During tapping, there is an increase in the process of neurotransmitter signal travel, which reduces the regulation of the hypothalamic-pituitary-adrenal Axis (HPA axis), thereby reducing the production of stress hormones. This research method uses a case study, and pre-and post-implementation measurements are carried out. The sample used was one person. The research sample was given treatment, namely SEFT therapy, to reduce anxiety levels. The results of SEFT therapy were observed using the State-Trait Anxiety Inventory (STAI) measuring instrument. There was a decrease in anxiety levels before and after treatment; namely, the STAI score decreased to 31 (moderate anxiety). SEFT therapy can reduce anxiety because the tapping mechanism in SEFT therapy has the function of releasing endorphin hormones. Endorphin hormones help reduce psychological symptoms such as anxiety.